Hexane extract from Spiranthera odoratissima A. St.-hil. leaves: chemical composition and its bioactive potential against Candida pathogenic species, Leishmania amazonensis and Xylella fastidiosa. Issue 11 (2nd June 2022) - Souza, Amanda de O.; Pereira, Paulo S.; Fernandes, Cassia C.; Andrade, Géssica; Pires, Regina H.; Candido, Ana C. B. B.; Magalhães, Lizandra G.; Vieira, Tatiana M.; Crotti, Antônio E. M.; Martins, Carlos H. G.; Miranda, Mayker L. D.
Abstract: Spiranthera odoratissima A. St.-Hil. (Rutaceae) has been popularly used against abdominal pain and rheumatism. This study aimed at extracting hexane from S. odoratissima (HE-SO) leaves to identify and quantify its volatile compounds by GC-MS and GC-FID and to evaluate its antifungal, antileishmanial and antibacterial activities in vitro . HE-SO exhibited antileishmanial activity against promastigote forms of Leishmania (Leishmania) amazonensis (IC50 = 38.16 µg/mL) and was moderately active against Xylella fastidiosa (MIC = 100 µg/mL). HE-SO also showed remarkable antifungal potential against six strains of Candida species, i. e., C. albicans, C. glabrata, C. parapsilosis, C. krusei, C. tropicalis and C. orthopsilosis . The lowest MIC values were between 31.25 and 250 µg/mL. Spathulenol (20.2%), τ-cadinol (11.7%), α-cadinol (9.4%), caryophyllene oxide (9.2%) and isoaromadendrene epoxide (8.2%) were the major components identified in HE-SO. Therefore, results showed that HE-SO has promising antileishmanial and antifungal actions. Graphical Abstract: UF0001